Nine practices of 21st century leadership : a guide for inspiring creativity, innovation, and engagement - DePaul, Gary A. (CRC Press, 2016)
"Derived by analyzing some of the best contemporary writers and thinkers on leadership, the book describes leadership practices that anyone can apply to improve morale, productivity, and performance"--Cover description